2018
DOI: 10.1161/jaha.118.009339
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Acute Myocardial Infarction Patients Included in the Hospital Readmissions Reduction Program

Abstract: BackgroundMedicare's Hospital Readmissions Reduction Program assesses financial penalties to hospitals based on risk‐standardized readmission rates after specific episodes of care, including acute myocardial infarction. Detailed information about the type of patients included in the penalty is unknown.Methods and ResultsStarting with administrative data from Medicare, we conducted physician‐adjudicated chart reviews of all patients considered 30‐day readmissions after acute myocardial infarction from July 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Acute MI is one of six conditions included in the HRRP, with a combined total of $528 million being withheld from hospitals due to readmissions in 2017 8 . Of all readmitted patients with MI contributing to the HRRP penalty, about 10% may have actually had type 2 MI 8,11 . In conjunction with the Hospital Value‐Based Purchasing Program, and after strict adjudication with physician medical record reviewers using the most current universal definition of MI, 7 McCarthy et al found that approximately 41% of patients with nonischemic myocardial injury are frequently misdiagnosed and subsequently billed as having type 2 MI 10 .…”
Section: Distinguishing Differences In MI Classificationmentioning
confidence: 99%
“…Acute MI is one of six conditions included in the HRRP, with a combined total of $528 million being withheld from hospitals due to readmissions in 2017 8 . Of all readmitted patients with MI contributing to the HRRP penalty, about 10% may have actually had type 2 MI 8,11 . In conjunction with the Hospital Value‐Based Purchasing Program, and after strict adjudication with physician medical record reviewers using the most current universal definition of MI, 7 McCarthy et al found that approximately 41% of patients with nonischemic myocardial injury are frequently misdiagnosed and subsequently billed as having type 2 MI 10 .…”
Section: Distinguishing Differences In MI Classificationmentioning
confidence: 99%
“…Thirty-day readmission rates for myocardial injury in this study are higher than the national 30-day readmission rates for acute MI (21% vs 14.8%), 5 and many patients with T2MI are included in Hospital Readmission Reduction Program penalties. 6 Because the methods for these programs effectively compare hospitals against one another, hospitals that include highrisk patients with myocardial injury as having T2MI may perform more poorly in value-based payment programs. Alternatively, because patients with myocardial injury may have more comorbidities than the general MI population, including patients with myocardial injury patients could conceivably reduce risk-standardized mortality and readmission rates.…”
Section: Key Pointsmentioning
confidence: 99%
“…Approximately 40% of readmissions were due to infectious or bleeding complications, and non-cardiovascular causes of rehospitalization outnumbered those due to cardiovascular reasons (11). Similarly, examining 30-day readmissions after type 2 MI, Martin and colleagues found that greater than a quarter of readmissions were due to infection and another quarter due to non-cardiac chest pain (3).…”
Section: Type 2 Myocardial Infarction: Patient Characteristics and Prmentioning
confidence: 99%
“…Thus, it seems unreasonable to hold hospitals accountable for readmission of these patients, in the absence of strategies to prevent repeat hospitalization. Indeed, many patients with type 2 MI will be readmitted for non-cardiovascular reasons related to their comorbidities (3,11).…”
Section: A Path Forwardmentioning
confidence: 99%
See 1 more Smart Citation